Efficacy of phenobarbital and sodium valproate in treating convulsive epilepsy in rural northeast China. (October 2019) - Li, Jing; Yang, Dan; Zhao, Danyang; Li, Nan; Lin, Weihong
Highlights: People with convulsive epilepsy in rural northeast China received a standardized treatment for free. Phenobarbital and sodium valproate were both effective for treating epilepsy in rural areas. Although confined to the challenged economy, we still tried our best to ensure the compliance. Abstract: Purpose: Phenobarbital and sodium valproate are broad spectrum and inexpensive antiepileptic drugs that are used to treat convulsive epilepsy. We examined the therapeutic effects of phenobarbital and sodium valproate in patients with convulsive epilepsy in the rural northeast China, and discuss our efforts to ensure patients' compliance. Methods: Patients with convulsive epilepsy were screened by trained township health center doctors. Patients in the phenobarbital group were enrolled between January 2011 and December 2012, and followed up until December 2017. Patients in the sodium valproate group were enrolled between January 2011 and December 2017, and followed up for 1 year. Efficacy of phenobarbital or sodium valproate was assessed by the reduction in seizure frequency. Results: A total of 1200 patients were diagnosed by screening and rechecking, of which 925 patients received phenobarbital and 275 received sodium valproate. In the phenobarbital group, 528 patients were followed up for ≥60 months, and the efficacy rates of reduction of seizure frequency by at least 75% was in the fifth year. In the sodium valproate treatment group, 228 patients were followed up for 12 months, and the reduction of seizure frequency by at least 75% was 60.4%. 444 patients (37%) did not complete the study. Dizziness (27%) was a common adverse event in phenobarbital group. In the sodium valproate group, gastrointestinal complaints (27.3%) was a common adverse event. Conclusion: Phenobarbital and sodium valproate were proven to be efficacious in treating convulsive epilepsy in rural northeast China. The patients' compliance still needs to be improved.